2022
DOI: 10.47895/amp.v56i1.3865
|View full text |Cite
|
Sign up to set email alerts
|

State and Trends of Occupational Health and Safety in the Philippines

Abstract: Introduction. In the Philippines, industries began to recognize the importance of workers’ health after occupational safety and health were introduced in the early 1900s. Ever since, several legal bases have existed to protect the people’s welfare. However, data regarding this matter is limited in the country. Objective. This paper aimed to develop a comprehensive review of occupational safety and health data, including hazard exposures and occupational diseases for various Filipino occupational groups.&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Para Politis et al (2023) afirman que establecen los requisitos y obligaciones que las organizaciones deben cumplir para garantizar entornos laborales seguros y saludables para sus trabajadores. De la misma forma Saad & Al-Naggar (2023); Akomah & Ramani (2023); Lu (2022) señalan que las normativas son las regulaciones, leyes y estándares establecidos por las autoridaldes competelntes en correlación con la seguridlad y saluld en el trabajo; es la provisión de requisitos y supervisión de las autoridades para el desarrollo de entornos seguros y saludables para los trabajadores.…”
Section: Discussionunclassified
“…Para Politis et al (2023) afirman que establecen los requisitos y obligaciones que las organizaciones deben cumplir para garantizar entornos laborales seguros y saludables para sus trabajadores. De la misma forma Saad & Al-Naggar (2023); Akomah & Ramani (2023); Lu (2022) señalan que las normativas son las regulaciones, leyes y estándares establecidos por las autoridaldes competelntes en correlación con la seguridlad y saluld en el trabajo; es la provisión de requisitos y supervisión de las autoridades para el desarrollo de entornos seguros y saludables para los trabajadores.…”
Section: Discussionunclassified
“…This places a lot of significance on comprehending and mitigating exposure to hazards at the workplace. Despite this, most workers, particularly, those in the informal sector work under unfavourable conditions such as poor lighting, inadequate working space, and poor ventilation which predispose them to work-related diseases, accidents and injuries [ 2 , 3 ]. A report by the International Labour Organization showed that over 2.3 million employees suffer work-related illnesses, accidents and injuries every year; claiming over 6000 lives every day globally [ 4 ].…”
Section: Introductionmentioning
confidence: 99%